ANALISA NILAI PENDIDIKAN SURAT AS-SHAFFAT AYAT 102 MENURUT TAFSIR IBNU KATSIR - Ima Liana; Nurul Hidayah; Afif Kholisun Nashoih (Al-Lahjah, 2020)
The purpose of this paper is to find out (1) the values ​​of Islamic education contained in verse as-saffat verse 102 (2) the application of Islamic law educational values ​​contained in verse as-saffat verse 102 in classroom learning. This type of research is library research with a qualitative descriptive approach. The method in this study is exploratory, namely to find the meaning of educational values ​​contained in surah as-saffat verse 102 from various books of interpretation including the book of tafsir Ibn Kathir by M. Quraish Shihab. The results of the study show that the values ​​of Islamic education contained in Surah As-Saffat verse 102 are monotheism education (aqidah), democratic consultation education (syari'ah), and moral education.